Model Bisnis dan Integrasi Rantai Nilai dalam Industri Konstruksi Modular di Indonesia - Prasojo, Lugas Bijak; Fatima, Ima (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
The modular construction business model in Indonesia remains fragmented and lacks end-to-end integration, which hinders its efficiency and scalability. This study aims to compare the existing business model with an integrated ideal model, while identifying value chain inefficiencies caused by industry fragmentation. The research method involves mapping the Business Model Canvas elements and analyzing the value chain of modular construction. The findings reveal inefficiencies due to the separation of design and production processes, limited partner manufacturing facilities, and the absence of national standards. This study recommends vertical and horizontal integration strategies to enhance coordination, standardization, and overall efficiency of the national modular construction system in response to sustainably growing large-scale demand.